Penetapan Kawasan Gunung Merapi Sebagai Taman Nasional Dan Hak-Hak Masyarakat Lokal - Sunarno Sunarno (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2007)
The existence of Merapi area cannot be separated from indigenous community, in which in general it represents DIY community and in particular it represents those who live near Merapi. The relationship between community and Merapi area forms ecological unity. However, a decree issued by Forestry Ministry No. 234 year 2004 is potential to disturb its harmonious relationship.The indigenous people have rights in managing National Park of Merapi Area (TNGM) covering those of economy, social, participation, which are legal by law. Unfortunately, those rights are not well introduced to the local people so that they are not aware of them. Having status as National Park of Merapi Area (TNGM) results in decreasing the rights of the indigenous people. Some approaches are carried out to empower the indigenous people in managing National Park of Merapi Area (TNGM) which include: supporting legal product, participative legal enforcement, holistic information, workshops, group discussions, and interest grouping in order that the people are able to enjoy their life.